If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (v + 4)(v + 6) = 0 Reorder the terms: (4 + v)(v + 6) = 0 Reorder the terms: (4 + v)(6 + v) = 0 Multiply (4 + v) * (6 + v) (4(6 + v) + v(6 + v)) = 0 ((6 * 4 + v * 4) + v(6 + v)) = 0 ((24 + 4v) + v(6 + v)) = 0 (24 + 4v + (6 * v + v * v)) = 0 (24 + 4v + (6v + v2)) = 0 Combine like terms: 4v + 6v = 10v (24 + 10v + v2) = 0 Solving 24 + 10v + v2 = 0 Solving for variable 'v'. Factor a trinomial. (6 + v)(4 + v) = 0Subproblem 1
Set the factor '(6 + v)' equal to zero and attempt to solve: Simplifying 6 + v = 0 Solving 6 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + v = 0 + -6 Combine like terms: 6 + -6 = 0 0 + v = 0 + -6 v = 0 + -6 Combine like terms: 0 + -6 = -6 v = -6 Simplifying v = -6Subproblem 2
Set the factor '(4 + v)' equal to zero and attempt to solve: Simplifying 4 + v = 0 Solving 4 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + v = 0 + -4 v = 0 + -4 Combine like terms: 0 + -4 = -4 v = -4 Simplifying v = -4Solution
v = {-6, -4}
| y=1/2(0)-2 | | -6x-6=-6+2x | | 4x+27=6x | | y=1/2(-2)-2 | | y=1/2(-4)-2 | | 10+5x=4x+64 | | 12x-7=10x+13 | | -8-4n=19 | | 2y-6=5y+9 | | 9p^3+73p+70=0 | | y=-1/4(-2)-6 | | x^2-y^2=41 | | -26=5x+9 | | -49+3y+9=2(3y-4)-8 | | 10+5x=-4x+64 | | 10n^2-29n+10=0 | | 13a-13=14a+5 | | -2m-7=-29 | | y=-1/4(-4)-6 | | 8x+13=53 | | 72=-8(r-2) | | a-b=7 | | 3.7x-8.5=13.7 | | y=-1/4(5)-6 | | 2x^2+27x-7.5=0 | | 6x-2=-32 | | 5=3(x-2)-(x-7) | | 2m+12=3m-21 | | -4a-5=-9 | | 2=(4x-2)(2-x) | | 3x^2+x-9=0 | | -2+4x=10 |